2010 IEEE Global Telecommunications Conference GLOBECOM 2010 2010
DOI: 10.1109/glocom.2010.5683862
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Games for Distributed Radio Access Selection in Broadband Networks

Abstract: Nowadays networks are characterized by the abundance of diverse Radio Access Interfaces (RAI) in the same operating area. The various wireless interfaces can belong to the same Radio Access Technology or not. In such a scenario, a mobile user will be able to select selfishly one of the available radio interfaces in order to enhance its own performance. Therefore, the radio access selection policy is vital and must be designed astutely to avoid resource wastage. In this paper, the RAI selection process is appre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…(8) implies that user n prefers being a member of coalition S α ⊆ N (t) with n ∈ S α over coalition S β ⊆ N (t) with n ∈ S β ,or at least, n prefers both coalitions equally. Furthermore, we propose an incremental preference function f n for any user n ∈ N (t) and any coalition S k such that n ∈ S k : (9) where user m ∈ S k \ {n} and φ n (S k ), φ m (S k \ {n}) is the payoff received by each user in coalition given by (7).…”
Section: B Hedonic Game Settingmentioning
confidence: 97%
See 3 more Smart Citations
“…(8) implies that user n prefers being a member of coalition S α ⊆ N (t) with n ∈ S α over coalition S β ⊆ N (t) with n ∈ S β ,or at least, n prefers both coalitions equally. Furthermore, we propose an incremental preference function f n for any user n ∈ N (t) and any coalition S k such that n ∈ S k : (9) where user m ∈ S k \ {n} and φ n (S k ), φ m (S k \ {n}) is the payoff received by each user in coalition given by (7).…”
Section: B Hedonic Game Settingmentioning
confidence: 97%
“…Therefore, by inspecting (7), (8)and (9), we have Property 2: The proposed network selection coalition formation game is reformulated as a hedonic coalition formation game (N, ), with the preference relation n given by (8) for any user n ∈ N (t).…”
Section: B Hedonic Game Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…In LTE, WLAN and VLC standards, the user achieved instantaneous rate is discrete, which is determined by the user's location and varies with the fading effect over time. Similar to the lecture [15], we make a set of discrete achievable peak rates 1, 2, , We use the uplink dominant traffic to examine the convergence performance of the proposed algorithm. Since observation 1 has revealed that the uplink of VLC could hardly support the high uplink performance requirement, we can remove VLC to reduce the action space.…”
Section: Performance Evaluatiionmentioning
confidence: 99%